Genetic and Functional Analyses of Virulence Potential of an Escherichia coli O157:H7 Strain Isolated From Super-Shedder Cattle - Teng, Lin; Lee, Shinyoung; Park, Dongjin; Jeong, Kwangcheol Casey (Frontiers in Cellular and Infection Microbiology, 2020)
Shiga toxin (Stx)-producing Escherichia coli (STEC) O157:H7 is an enteric pathogen that causes life-threatening disease in humans, with cattle being major natural reservoirs. A group of STEC O157:H7 with a dramatic combination of high virulence potentials and super-shedder bovine origin have been isolated. Here, an STEC O157:H7 isolate, JEONG-1266, was analyzed by comparative genomics, stx genotyping, and phenotypic analyses. The phylogenetic typing and whole-genome comparison consistently showed that JEONG-1266 is genetically close to EC4115 (one of 2006 Spinach outbreak isolates) and SS17 (an isolate from super-shedder cattle) strains, all of which belong to lineage I/II and Clade 8. Both lineage I/II and Clade 8 are known to be mostly associated with clinical strains with high virulence and severe clinical symptoms. Further, JEONG-1266, like EC4115 and SS17, harbors stx2a/stx2c genes, and carries Stx-encoding prophages, specifically the φstx2a-γ subtype. Possession of the φstx2a-γ subtype of Stx-encoding prophages and production of Stx2a have been shown to be a key signature associated with hypervirulent STEC O157:H7 strains. In silico virulence typing elucidated JEONG-1266, EC4115, and SS17 shared a highly conserved profile of key virulence genes at the nucleotide sequence level. Consistently, phenotypic data showed that JEONG-1266 expressed a high level of Stx2 toxins and had the full capacity of adhesion in vitro. Taken together, our study suggests that JEONG-1266 may represent an emerging STEC O157:H7 group, which are hypervirulent strains that originate from super-shedders, that can be a threat to food safety and public health.